2017
DOI: 10.1021/acs.nanolett.7b00254
|View full text |Cite
|
Sign up to set email alerts
|

Semiconductor Seeded Nanorods with Graded Composition Exhibiting High Quantum-Yield, High Polarization, and Minimal Blinking

Abstract: Seeded semiconductor nanorods represent a unique family of quantum confined materials that manifest characteristics of mixed dimensionality. They show polarized emission with high quantum yield and fluorescence switching under an electric field, features that are desirable for use in display technologies and other optical applications. So far, their robust synthesis has been limited mainly to CdSe/CdS heterostructures, thereby constraining the spectral tunability to the red region of the visible spectrum. Here… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
82
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 62 publications
(88 citation statements)
references
References 36 publications
3
82
0
3
Order By: Relevance
“…[107][108][109] An increased biexciton lifetime was observed that correlates with the reduced Auger rate.T he importance of the grading interface was also shown for other dimensionalities,a ss een in CdSe/ Cd 1Àx Zn x S-seeded nanorods with ar adially graded composition that show bright and highly polarized green emission with minimal blinking. [41] These observations provide direct experimental evidence that, in addition to the size of the quantum dot, its interfacial properties also significantly affect the rate of Auger recombination and can be used as an additional parameter for tuning the optical properties of SCNCs for display applications.…”
Section: Fluorescence "Blinking" and Its Suppressionmentioning
confidence: 84%
See 1 more Smart Citation
“…[107][108][109] An increased biexciton lifetime was observed that correlates with the reduced Auger rate.T he importance of the grading interface was also shown for other dimensionalities,a ss een in CdSe/ Cd 1Àx Zn x S-seeded nanorods with ar adially graded composition that show bright and highly polarized green emission with minimal blinking. [41] These observations provide direct experimental evidence that, in addition to the size of the quantum dot, its interfacial properties also significantly affect the rate of Auger recombination and can be used as an additional parameter for tuning the optical properties of SCNCs for display applications.…”
Section: Fluorescence "Blinking" and Its Suppressionmentioning
confidence: 84%
“…Based on these considerations,i tseems that SCNCs with an alloy composition, such as Zn x Cd 1Àx S, Zn x Cd 1Àx Se,o r CdSe x S 1Àx /Zn x Cd 1Àx Sd ot-in-rod structures, [41] which offer confined potential against the electric field and ar eduction of Auger nonradiative recombination by smoothing the confinement potential, would be the ideal choice for an emitter in an EL QD-LED.I ndeed, relatively high efficiencies in QD-LEDs have been reported with multilayered alloyed structures such as Zn x Cd 1Àx Se/ZnS,Z n x Cd 1Àx Se/ Zn x Cd 1Àx S, and Zn x Cd 1Àx Se. [139,142,155] Recently,Y ang et al reported af ull series of blue,g reen, and red QD-LEDs,a ll with EQE values over 10 %b yu sing graded-shell Cd 1Àx Zn x Se 1Ày S y as well as an ETL of ZnO nanoparticles in "hybrid CTL"a rchitectures.…”
Section: Electroluminescent Displays With Colloidal Scncsmentioning
confidence: 99%
“…Nanoscale heterostructures which incorporate two or more materials such as in core–shell nanocrystals, core‐crown nanoplates, or seeded nanorods, allow better control of the optical, electrical, and magnetic phenomena that is inaccessible in single component nanoparticles. In NPL heterostructures, the most attractive features are the possibility of a spatial separation of holes and electrons in core–shell NPLs, and efficient exciton collection and rapid transfer to the core in core‐crown NPLs .…”
Section: Resultsmentioning
confidence: 99%
“…The optical density of QRs in the film was measured as 1.2 at 460 nm. The QRs used in this study showed PL quantum yield of 70% which is lower than the ones in some recently published reports . Such films fabricated with QRs having much higher PL quantum yield and increased polarization ratio are expected to enhance the optical efficiency of the LCD device up to 7% .…”
mentioning
confidence: 66%